Is Extreme Poverty in Indonesia is Going to End? - Darma, Amdi Veri; Wicesa, Nayaka Artha; Setyanti, Axelllina Muara; Rochmat , Teguh Maulidi (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2024)
Purpose This research aims to analyze and project extreme poverty in Indonesia. Through the method of descriptive statistical analysis and cluster analysis, it is found that the rate of decreasing in the extreme poverty rate is higher than the rate of decreasing in non-extreme poverty Design/methodology/approach The methods used to answer research problems are descriptive statistical analysis, econometric forecasting model analysis, and cluster analysis. Findings It is found that the rate of decreasing in the extreme poverty rate is higher than the rate of decreasing in non-extreme poverty. In addition, through forecasting analysis it is also found that Indonesia will be able to reduce extreme poverty to 0.30% in 2024. However, the decreasing in extreme poverty to zero percent in 2024 will be realized if the acceleration of handling extreme poverty is carried out in an integrated way through the collaboration of two interventions of extreme poverty reduction program group, that are reducing expenses and increasing income Research limitations/implications This research is expected to be a positive reference for the Indonesian government in implementing extreme poverty reduction policies to zero percent in 2024. Originality/value This research addresses the President of Indonesia's goal of achieving zero percent extreme poverty by 2024, filling a gap in existing studies. Its significance lies in evaluating the feasibility of this ambitious target.